Exploring EFL Preservice Teachers’ Directive Speech Act in Classroom Interaction During Teaching Internship - Catur Kepirianto; Siti Mariam (Soegijapranata Catholic University, 2025)
This qualitative descriptive study investigated the types and functions of directive speech acts produced by EFL preservice teachers during teaching internship. Data were collected through classroom observation and documentation, then analyzed through data selection, reduction, display, and verification. The participants were three EFL preservice teachers at public and private Islamic secondary schools and in Semarang city. It explored them by examining their types, linguistic forms, interactional functions, and politeness strategies within actual classroom interaction. The findings indicate that preservice teachers frequently rely on a range of directive types, including commands, instructions, requests, suggestions, prohibitions, and interrogatives functioning as directives. Among these, instructions and commands were the most dominant, reflecting their need to manage classroom activities and guide students through learning tasks. The results show that there were 144 preservice teachers’ utterances of directive speech acts. They consist of 23% requests, 21% questions, 17% requirements, 13% prohibitions, 8% permissions, and 18% advisories. It can be concluded requests are the most dominant of what teachers say. It means that preservice teachers concern on student engagement; establish an interactive learning environment; adapting learning to student needs, cultivate discipline and responsibility. Overall, the frequent use of request-type directive speech acts by teachers shows efforts to create an effective and student-centered learning environment. The study highlights the importance of pragmatic competence in teacher education programs. Preservice teachers need explicit training on how to use directive speech acts strategically to enhance communication effectiveness while maintaining positive preservice teacher–student rapport. Findings suggest the need to integrate pragmatics-based microteaching in teacher preparation programs, focusing on directive strategies, politeness formulas, and context-sensitive language use. Enhanced awareness of directive forms can support preservice teachers in fostering learner-centered interaction, such as using prompts and suggestions instead of only commands